Analysis environmental impact on slope protection constructions and environmental friendly solutions of slope protection rehabilitation - Šadzevičius Raimondas; Vaitiekūnas Antanas (2012)
There were investigated 32 Lithuanian earth dam slopes protected with concrete in the years 1998–2011. The purpose of these investigations, based on research in the field, is to evaluate the impacts of environment on reinforced concrete slabs for earth dam slope protection by establishing character and causes of the main deteriorations and ruptures in the slabs. Further goal is to evaluate frost impact on the change of concrete properties and durability of covering layer of the slabs and to suggest environmental friendly solutions of slope protection rehabilitation. During expeditions the structures were visually examined on location and their most deteriorated places were detected, typical defects and deteriorations were measured. Furthermore, regularities of concrete compression strength and water absorbability of reinforced concrete slabs for earth dam slope protection under the influence of freezing–thawing cycles and other environmental factors were determined. Using the durability evaluation method of reinforced concrete slabs for earth dam slope protection created by us, the period left to use the construction till the probable deterioration start (T5%) or end (T50%) may be calculated. Environmental friendly solution for the rehabilitation of slope protection structures is proposed.
Keywords: Műszaki és technológiai tudományok; Környezetmérnöki tudományok